P(p-3)4=-2

Simple and best practice solution for P(p-3)4=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P(p-3)4=-2 equation:


Simplifying
P(p + -3) * 4 = -2

Reorder the terms:
P(-3 + p) * 4 = -2

Reorder the terms for easier multiplication:
4P(-3 + p) = -2
(-3 * 4P + p * 4P) = -2
(-12P + 4pP) = -2

Solving
-12P + 4pP = -2

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Reorder the terms:
2 + -12P + 4pP = -2 + 2

Combine like terms: -2 + 2 = 0
2 + -12P + 4pP = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(1 + -6P + 2pP) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(1 + -6P + 2pP)' equal to zero and attempt to solve: Simplifying 1 + -6P + 2pP = 0 Solving 1 + -6P + 2pP = 0 Move all terms containing P to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -6P + -1 + 2pP = 0 + -1 Reorder the terms: 1 + -1 + -6P + 2pP = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -6P + 2pP = 0 + -1 -6P + 2pP = 0 + -1 Combine like terms: 0 + -1 = -1 -6P + 2pP = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 10x=8(x-9) | | 5x+6=3x+5 | | 4x+7+2x+16=7x+2 | | 3r^3-15r^2+18r=0 | | 2x^4-9x^3+13x^2-x-5=0 | | 0=-6t^2+13t+5 | | 12x^2+15x^2=X | | x^2+bx+18=0 | | (5x-4)(7x-5)=0 | | .2(x-6)=2 | | 15k+k-21=105 | | 6q-178=2(6-4q)-5q | | -3w^2+4w=56 | | 4w^7+22w^6+10w^5= | | -3(x+5)=3(-1) | | 92=4/x | | x^1/3x^1/7 | | n+-4+-9= | | -18x-36+36-12x=-14 | | (x-17.7)+19.6=17.8 | | (4X-10)=(X) | | X^2/x+4=16/x+4 | | 7x^3-x^2-56x+8=0 | | 3d+1=-5 | | r^2s^4t^6/r^3s^4t^-6 | | x-5y-25=0 | | 4s-72=2(6-3s)-4s | | (2/x)/(1/2x) | | s/6-6=12 | | (5t^2-t-8)(2t^2+5t-1)= | | 20-0=10o-2 | | 1/2y-1/3(y-1)=5y |

Equations solver categories